Investigating the Effect of Social Capital on Household’s Poverty in Khyber Pakhtunkhwa, Pakistan - Tahir Iqbal; Dr. Ihtisham ul Haq; Alam Khan (International Journal of Business and Economic Affairs, 2023)
Poverty is one of the sustainable development goals, and mostly the developing world is suffering from high poverty rates. Pakistan being a developing country, is also facing a high poverty rate. Poverty can be gauged through objective, subjective and time-based aspects; however, objective poverty is related to income and documented in official statistics. This study is related to objective poverty and investigates the impact of social capital on Poverty in Khyber Pakhtunkhwa. This study also performs a comparative analysis of rural and urban areas of Khyber Pakhtunkhwa. Primary data has been collected through a well-structured questionnaire. The sampling size is decided on the well-known Yamane formula, and this is followed by a multi-stage stratified random sampling method. This study analyzed the data from 392 valid respondents. This study constructs social capital on seven dimensions and estimates poverty level and social capital, followed by logistic regression analysis. Gender, human capital, employment ratio, female-male ratio and size of household are control variables in the study. The logistic regression results show that social capital, employment ratio, human capital, gender of the household and size of household are significant factors of Poverty in Khyber Pakhtunkhwa. Moreover, an increase in social capital, employment ratio and human capital results in less poverty, while the household size and female-male ratio led to increasing the chances of being poor. Additionally, results indicate that social capital is more effective in rural areas, while employment ratio and human capital are more effective factors in alleviating poverty in urban areas. The findings of this study explain and signify the level of poverty occurrence in Khyber Pakhtunkhwa and also highlights factors of poverty; thus, the policy implications of the study will be helpful in addressing poverty. It is recommended that policy measures must enhance social capital along with human capital for poverty alleviation.